1980
DOI: 10.1111/j.1600-0773.1980.tb01554.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Factor XII in Plasma from Rats Pretreated with Tranexamic Acid. Inhibition of a Plasmin‐induced Loss of the Functional Activity of High Molecular Weight Kininogen

Abstract: Incubation of plasma from rats pretreated with tranexamic acid (40 mg/l 00 g) with acetone (23 % v/v) yielded enzyme preparations in which all the plasminogen present was recovered as plasmin and a plasmin‐like substance without affinity for lysine‐Sepharose. This substance, designated “plasmin”, was separated from plasmin and kallikrein in a three‐step procedure using columns of lysine‐Sepharose, DEAE‐Sephadex A‐50, and arginine‐Sepharose. The ratios of fibrinolytic, caseinolytic, LEe esterase, BAEe esterase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1980
1980
1983
1983

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Using the lastmentioned procedure, it has previously been shown that the PKA level was significantly lowered in rat plasma by intravenous injection of dextran, or by chromatography on a lysine-Sepharose column (Briseid & Berstad 1979;Briseid et a/. 1979), and evidence was later provided that such a lowering could be due to a conversion of HMWK into a nonfunctional state, probably by plasmin or a plasminlike substance (Briseid & Ryssdal 1980). Kinin release experiments with plasma kallikrein carried out in parallel showed that the kinin part of HMWK was retained after column passage (Briseid et a/.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the lastmentioned procedure, it has previously been shown that the PKA level was significantly lowered in rat plasma by intravenous injection of dextran, or by chromatography on a lysine-Sepharose column (Briseid & Berstad 1979;Briseid et a/. 1979), and evidence was later provided that such a lowering could be due to a conversion of HMWK into a nonfunctional state, probably by plasmin or a plasminlike substance (Briseid & Ryssdal 1980). Kinin release experiments with plasma kallikrein carried out in parallel showed that the kinin part of HMWK was retained after column passage (Briseid et a/.…”
Section: Discussionmentioning
confidence: 99%
“…Human plasma prekallikrein was partially purified, as described by Laake & Vennersd (1973a), and diluted to about 6 BAEe-U/ml. High molecular weight kininogen (HMWK) was prepared as described by Briseid & Ryssdal (1980). Assay of kininogen fractions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation